2019
DOI: 10.24875/reie.19000008
|View full text |Cite
|
Sign up to set email alerts
|

Volumen plaquetario medio como predictor de mortalidad en pacientes con sepsis y choque séptico en urgencias

Abstract: Artículo de InVestIgAcIón orIgInAl resumenIntroducción: La determinación del volumen plaquetario medio (VPM) es sencilla, de bajo costo y fácil acceso, y es un predictor de mortalidad en diversas patologías. El objetivo del presente estudio fue identificar si el VPM es un predictor de mortalidad en pacientes con sepsis y choque séptico en el Servicio de Urgencias. Metodología: Se diseñó un estudio observacional, retrospectivo y transversal en pacientes con sepsis y choque séptico del Servicio de Urgencias del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the predictive utility of MPV in sepsis [ 4 , 11 – 16 ], Vardon-Bounes F, et al [ 17 ], reported MPV as a predictor of mortality (HR = 3,79) at 90-day survival study. Additionally, a meta-analysis performed by Tajarernmuang P. et al [ 18 ], reported 11 studies (n = 3724), in which a significant association was determined between the MPV and mortality in critically ill patients on day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the predictive utility of MPV in sepsis [ 4 , 11 – 16 ], Vardon-Bounes F, et al [ 17 ], reported MPV as a predictor of mortality (HR = 3,79) at 90-day survival study. Additionally, a meta-analysis performed by Tajarernmuang P. et al [ 18 ], reported 11 studies (n = 3724), in which a significant association was determined between the MPV and mortality in critically ill patients on day 3.…”
Section: Discussionmentioning
confidence: 99%